Baseline and status of desertification in Central Asia. (21st February 2022) - Cai, Diwen; Wang, Xunming; Hua, Ting; Jiao, Linlin; Geng, Xin
Abstract: Baseline determination is a prerequisite for desertification monitoring and assessment and also for the sustainable development of drylands. In this study based on long‐term remote sensing net primary production (NPP) data and combined with a local NPP scaling method, the desertification status in Central Asia is quantified, and NPP‐based objective baseline of desertification (potential NPP, NPPp ), which could be more convenient and enables the desertification status measurable from local to global scales, is established by integrating space‐for‐time substitution, isolation forest (iForest) algorithm, and Monte Carlo simulations. More reliable than a fixed percentile‐based reference with subjective preference, the analyzed results show that across Central Asia over the past four decades, the NPPp ranged from 46.4 to 639.5 gC m −2  yr −1 with different land cover types and regions, and the general desertification status in the region was rated as a moderate degree with an average of 50.5%. From the 1980s to the 2000s in most regions of Central Asia, reversals of desertification occurred, but it intensified in the 2010s. This study may contribute to improving the existing framework of SDG Indicator 15.3.1.